Imagined communities and practiced geopolitics - Van Der Wusten, Herman (Hungarian Geographical Bulletin, 2015)
Political geographers have done a lot of work on both 'nationalism' and 'geopolitics' but they have by no means been the only users of these terms. Based on the massive data-set collected by Google's book digitization program the paper first draws a quick picture of the spread of these terms in different languages since 1900. It then provides some analysis of the substance of these terms as used in the social science literature and in political geography in particular. In a next section the current Ukrainian conflict formation is introduced as a case to illustrate the usefulness of these concepts. Internal Ukrainian relations are taken into account with respect to nationalist sentiment as well as geopolitical practice as well as the contrary geopolitical visions of the major external actors involved. Some suggestions on the shifting significance of nationalism and geopolitics are finally made as a consequence of changed circumstances resulting from globalization and the concomitant weakening of the national state as the firm foundation of the political order.